THE EFFECT OF JOB SATISFACTION AND SUPERVISION ON THE PERFORMANCE OF VILLAGE ASSISTANTS IN KUPANG REGENCY WITH WORK DISCIPLINE AS A MEDIATING VARIABLE - Yosafat Dokubani; Simon Sia Niha; Daniel Taolin (SEAN Institute, 2023)
The purpose of this research is to obtain an overview of the performance of village assistants in Kupang Regency, seen from the elements of work discipline, job satisfaction and supervision of village assistants in Kupang Regency. This research uses quantitative methods. The research sample was 48 village assistants in Kupang Regency. Data was collected by distributing questionnaires and analyzed using descriptive and inferential statistics using the SmartPLS application. The results of descriptive statistical analysis show that the performance variable is in the good category, work discipline is quite good, job satisfaction is good and supervision is quite good. The results of inferential statistical analysis show that job satisfaction and supervision have a significant effect on work discipline variables. Furthermore, work discipline, job satisfaction and supervision have a significant effect on performance variables.